Development of a Civics Learning Model Based on Civic Altruism in Higher Education to Realize Civic Equality for Disability - Nanggala, Agil; Saadah, Dodoh Siti; Fahmi, Rizal (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2026)
This research seeks to develop a civics learning model based on civic altruism in higher education to realize civic equality for disability, considering that the existence of disabilities is consistently discriminated against or marginalized due to the stereotype of ableism, which views disability as a disability, disgrace, burden, and useless, so it needs to be overcome through civics learning based on civic altruism, because it is holistic and integrative. This research is based on a qualitative approach, with grounded theory methods, namely problem formulation, relevant theory analysis, data collection, data analysis, and conclusion. Data analysis includes reduction, display, and verification. The time for the research is December 2023 to February 2024. Research results: 1) The development of a civics learning model based on civic altruism in higher education to realize civic equality for disability is holistic, inclusive, participatory, innovative, and humanist, because it contains the character of altruistic, which prioritizes the public interest and humanitarian action, including realizing disability civic equality, through the concept and practice of civics learning in higher education, as civic education and citizenship education, which is democratic and persistent against the stereotype of ableism, including mandating students and people with disabilities as learning subjects; 2) The civics learning model based on civic altruism to realize civic equality for disabilities through the practice of citizenship education contains service-learning and pentahelix collaboration, as a civic campaign or a real collaborative effort in realizing civic equality and civic empowerment of disabilities based on civic altruism, thus reflecting the character of students who are voluntary, humanist, and civilized. The novelty of the research, namely the completion of the development of a civics learning model based on civic altruism in higher education to realize civic equality for disabilities, because it has never been researched through any research, it becomes a new applied theory, including a new paradigm that is integrative and transformative through civics learning based on civic altruism, to overcome the stereotype of ableism, as a source of disability discrimination.